Sponges from Clipperton Island, East Pacific - van Soest, Rob W. M.; Kaiser, Kirstie L.; van Syoc, Robert (Zootaxa, 2011)
Twenty sponge species (totalling 190 individuals) were collected during the 1938, 1994 and 2004/5 expeditions to the remote island of Clipperton in the East Pacific Ocean. Seven species are widespread Indo-Pacific sponges; nine species comprise sponges new to science; four species were represented only by small thin patches insufficient for proper characterization and could be only determined to genus. The new species may not be necessarily endemic to the island, as several show similarities with species described from elsewhere in the East and West Pacific. Four species: Tethya sarai Desqueyroux-Faúndez & Van Soest (1997), Callyspongia (Callyspongia) roosevelti n.sp., Spongia (Spongia) sweeti (Kirkpatrick, 1900) and Suberea etiennei n.sp. were found commonly occurring in localities around the island in depths between 10 and 55 m, growing on dead corals, under overhangs and rubble stones. The remaining sponges were either rare or were thinly encrusting on coral fragments. The latter may be more abundant than appears from the present study as they are probably not easily observed. The sponge fauna of Clipperton Island shows strongest affinities with the Central and West Pacific regions and only two or three species are shared with the East Pacific region.